Jamming Resilient Cross-Layer Resource Allocation in Uplink HARQ-Based SIMO OFDMA Video Transmission Systems - Shu-Ming Tseng; Yung-Fang Chen; Po-Hsiang Chiu; Hung-Chang Chi (IEEE Access, 2017)
The cross-layer resource assignment algorithm of orthogonal frequency division multiple access (OFDMA) video communication systems by Wang et al. allocates the power and subcarriers according to both the layer 1 channel state information and the layer 5 rate distortion function. We introduce the hybrid automatic repeat request (HARQ) in layer 2 and a single-input multiple-output (SIMO) anti-jamming technique in layer 1, and propose an anti-jamming power/subcarrier assignment scheme crossing layers 1, 2, and 5 for HARQ-based SIMO OFDMA uplink video communication networks. We derive the new optimal condition for anti-jamming cross-layer resource allocation analysis, and thus propose a novel resource allocation method crossing layers 1, 2, and 5 by considering the angle between the jammer channel vector and the sender (desired signal) channel vector. By HARQ, we can increase the target symbol error rate without increasing the rate of the packet error, more bits can be transmitted, and the peak signal-to-noise ratio (PSNR) (the video quality) is improved. The results of the simulations show that the PSNR increases by 11.3 dB when we consider the angle between the jammer channel vector and the sender channel vector in the proposed resource allocation algorithm crossing layers 1, 2, and 5. The PSNR improves further by 1.8-2.6 dB when we add HARQ, when the average SNR = 18 dB and there are 12 users.